POUPAKIDS: AN EDUCATIONAL FINANCIAL APP FOR CHILDREN FOCUSED ON SAVINGS, RESPONSIBLE SPENDING, AND INVESTMENTS (CIPEEX, 2025)
PoupaKids is an educational app under development, created with the goal of promoting financial education among children aged 6 to 12. In Brazil, over 60% of the population struggles to control their spending and plan their finances, which reflects a lack of basic financial education from childhood. The app emerges as a solution to this problem, aiming to teach fundamental financial concepts such as saving, spending responsibly, and investing, through an interactive, engaging, and practical experience. The project was developed to make financial learning more accessible and understandable, using methods that capture children's attention and encourage practicing skills that will be useful in adulthood.The methodology of PoupaKids is based on gamification. Financial learning is presented through games and interactive challenges that teach children about the importance of saving, planning expenses, and making smart investments. One of the main features of the app is a virtual allowance, set by parents or guardians, which allows children to receive a regular amount of virtual money. This money can be used within the app to meet goals and earn rewards, such as games or toys. In this way, children learn to manage their allowance by making decisions about how much to spend and save to achieve their goals.In addition to games, PoupaKids offers a goals and rewards system. Children set personal financial goals, such as buying an item of their choice, and work to achieve these goals through saving. The app includes a virtual store with children's products, where they can simulate purchases and learn to manage budgets, prices, and change. This improves their math and financial skills in a fun way, teaching concepts such as financial planning and patience, and encouraging long-term thinking.The project follows an agile development approach, with regular iterations and continuous feedback from stakeholders, including children, parents, educators, and financial experts. The Scrum Master facilitates the process, ensuring that development efforts focus on delivering continuous value. The Product Owner defines and prioritizes product requirements to ensure that features meet both customer needs and market expectations.Currently, the app is in the prototyping phase, with development focused on key features such as the virtual allowance and educational games. Preliminary tests suggest that PoupaKids has the potential to significantly improve children's financial knowledge. Through questionnaires and assessments conducted before and after using the app, the goal is to measure knowledge retention and the positive impact on personal financial management. Parents play an important role in monitoring their children's progress and adjusting goals and rewards to encourage appropriate financial behavior.In conclusion, PoupaKids offers an innovative solution to the lack of financial education for children in Brazil, teaching financial skills from an early age in a fun and accessible way. The app aims to prepare children for a financially responsible adult life, empowering them to make more conscious decisions about their financial resources. This project could have a significant impact on future generations, fostering a more financially aware and prepared society.
Keywords: Financial education; Children; Savings; Gamification